Can the use of silver nanoparticles in dental implants increase its antimicrobial potency? - systematic review - Brice Joseph; Nessma Sultan; Soher Nagi Jayash (BMC Oral Health)
Abstract Background Silver nanoparticles (AgNPs) is a promising nanotechnological solution to prevent microbial colonization on dental implants, offering a promising avenue for combating implant-related infections and improving long-term treatment outcomes. Methods Using manual search and electronic databases such as PubMed Advanced Search and Google Scholar, a methodical search was carried out from 2013 to 2023 utilizing keywords, and inclusion and exclusion criteria to find pertinent papers addressing the research question “Can the use of silver nanoparticles in dental implants increase its antimicrobial potency?”. Critical Appraisal analysis for this review was done using risk of bias tool for in vitro studies: QUIN tool. Results Nine of the 122 articles that were retrieved underwent the three-step screening process before being chosen for the final analysis. QUIN Tool were used to evaluate the quality of the included in vitro studies. The summarized results from nine studies reveal the efficacy of AgNPs in inhibiting microorganisms and preventing biofilm formation on dental implants. In vitro tests demonstrate AgNPs’ ability to hinder bacterial growth associated with peri-implantitis. Various techniques, including surface modifications and nanostructure incorporations, exhibit promising antibacterial effects. Conclusions AgNPs show promise in inhibiting multidrug-resistant bacteria, enhancing dental implant biocompatibility, and reducing peri-implant diseases, benefiting clinical outcomes and limiting bacterial colonization.